BALANCE SCORECARD DALAM ANALISIS KINERJA KOPERASI (Studi Kasus pada Koperasi Unit Desa (KUD) Bayongbong Kabupaten Garut, Jawa Barat) - Gijanto Purbo Suseno; Nataliningsih Nataliningsih; Nuni Wahyuni (Jurnal Manajemen Industri dan Logistik (JMIL), 2018)
Village Unit Cooperative (KUD) Bayongbong Garut Regency, Wes Java, is a livestock cooperative whose business activities are multi purpose. The purpose of cooperatives is to improve the welfare of members in particular and society in general, in accordance with the interests and needs of its members. The purpose of this study is to measure the performance of cooperatives by using Balanced Scorecard and efforts to be done so that cooperatives can improve its performance. Balanced Scorecard is a rapid measurement and control management system, precise and comprehensive, consisting of four perspectives: financial, customer, internal business processes and learning and growth. The results showed that the non-financial perspective of internal business consisting of livestock food business, cooperation business with State Electricity Company (PLN), Convenience Store, have a better perspective with score score 372, compared with other perspective that is customer perspective with value 832 and growth learning perspective with score 492. Suggestions that can be submitted are independent KUD Bayongbong must be able to improve service for customers and employee satisfaction, provide adequate information system and provide learning or training for its employees